Contribution of the MexX-MexY-OprM Efflux System to Intrinsic Resistance in Pseudomonas aeruginosa - Masuda, Nobuhisa (American Society for Microbiology, 2000)
To test the possibility that MexX-MexY, a new set of efflux system components, is associated with OprM and contributes to intrinsic resistance in Pseudomonas aeruginosa, we constructed a series of isogenic mutants lacking mexXY and/or mexAB and/or oprM from a laboratory strain PAO1, and examined their susceptibilities to ofloxacin, tetracycline, erythromycin, gentamicin, and streptomycin. Loss of either MexXY or OprM from the MexAB-deficient mutant increased susceptibility to all agents tested, whereas loss of MexXY from the MexAB-OprM-deficient mutant caused no change in susceptibility. Introduction of an OprM expression plasmid decreased the susceptibility of the mexAB-oprM-deficient-/mexXY-maintaining mutant, yet caused no change in the susceptibility of a mexAB-oprM- and mexXY-deficient double mutant. Immunoblot analysis using anti-MexX polyclonal rabbit serum generated against synthetic oligopeptides detected expression of MexX in the PAO1 cells grown in medium containing tetracycline, erythromycin, or gentamicin, although expression of MexX was undetectable in the cells incubated in medium without any agent. These results suggest that MexXY induced by these agents is functionally associated with spontaneously expressed OprM and contributes to the intrinsic resistance to these agents.